Atmospheric-Driven and Intrinsic Interannual-to-Decadal Variability in the Kuroshio Extension Jet and Eddy Activities - Nonaka, Masami; Sasaki, Hideharu; Taguchi, Bunmei; Schneider, Niklas (Frontiers in Marine Science, 2020)
To investigate the influences of oceanic intrinsic/internal variability and its interannual-to-decadal modulations on the Kuroshio Extension (KE) jet speed and associated eddy activity, a ten-member ensemble integration of an eddy-resolving ocean general circulation model forced by the 1965–2016 atmospheric reanalysis is conducted. We found a distinct time–scale dependence in the ratio of forced and intrinsic variability of the KE jet speed. On the decadal time scale, the ratio of the magnitude of intrinsic variability to that of the atmospheric–driven variability is 0.73, suggesting it is largely atmospheric–driven. In contrast, on the interannual time scales, the KE jet speed has a large ensemble spread, indicating that it is strongly affected by intrinsic variability and has substantial uncertainty. For eddy activity, the ratios of atmospheric–driven and intrinsic variability also depend on the region. In the downstream KE [32°–38°N, 153°–165°E], variability in the atmospheric–driven eddy activity dominates (1.36 times) over the intrinsic variability on the decadal time scale, and is positively correlated with the current speed. Consistent with the westward propagation of atmospheric–driven jet speed anomalies shown by the ensemble mean, the eddy activity in the downstream KE region is correlated with the current speed variability in the central North Pacific 4 years earlier. This linkage is robust even for each ensemble member with the significant lagged correlation found in seven out of ten ensemble members as well as the ensemble mean (r = 0.59), suggesting the possibility of prediction of the eddy activity. In contrast, the eddy activity in the upstream KE [32°–38°N, 141°–153°E] shows a very large intrinsic and limited atmospheric–driven variability with a ratio of the former to the latter of 2.73. These results suggest that the intrinsic variability needs to be considered in the interannual variability of strong ocean jet. The dependence of these findings to the model specificities needs to be further explored.